2017
DOI: 10.23910/ijbsm/2017.8.1.1774
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sowing Dates and Stage of Pinching on Growth, Yield and Quality of Fenugreek (Trigonella foenum-graecum L.)

Abstract: An experiment entitled effect of sowing dates and stage of pinching on growth, yield and quality of fenugreek was carried out during September 2015 to March 2016 at RVSKVV College of Horticulture, Mandsaur, M.P., India, with 12 treatment combinations, comprising four dates of sowing 25 th September, 10 th October, 25 th October and 9 th November with three stages of pinching i.e., No pinching, Pinching at 25 Days after sowing (DAS), Pinching 35 DAS. These treatments were replicated thrice in split spot design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 1 publication
3
5
0
Order By: Relevance
“…This might be due to the fact that better vegetative growth was achieved due to early sowing and congenial climatic conditions availed by the crop during the growth period. Similar findings were also reported by Afroz et al [25] in mustard seed; Sowmya et al [37] and Anitha et al [27] in fenugreek.…”
Section: Number Of Branches Per Plantsupporting
confidence: 89%
“…This might be due to the fact that better vegetative growth was achieved due to early sowing and congenial climatic conditions availed by the crop during the growth period. Similar findings were also reported by Afroz et al [25] in mustard seed; Sowmya et al [37] and Anitha et al [27] in fenugreek.…”
Section: Number Of Branches Per Plantsupporting
confidence: 89%
“…Results from the experiment showed that the maximum weight of 1000-seed (12.58 g) was revealed from S 2 (15 November) treatment where the minimum weight of 1000-seed (10.22 g) was noted from the S 3 (30 November) treatment. The experiment's result coincided with the findings of [16] who reported that thousand seed weight, seed yield, straw yield, biological yield and harvest index were statistically influenced due to different sowing dates. Significant influence was observed on the weight of 1000-seed due to different levels of phosphorus during the experimentation (Table 6).…”
Section: Weight Of 1000-seed (G)supporting
confidence: 86%
“…Results from the experiment showed that the maximum weight of seeds per plant (5.40 g) was obtained from the S 2 (15 November) treatment which was statistically similar to the S 1 (1 November) treatment where the minimum weight of seeds per plant (4.89 g) was noted from S 3 (30 November) treatment. [16] found similar trends and stated that weight of pod, number of seeds pod -1 , the weight of seeds pod -1 and thousand seed weight was higher when early sowing. Significant influence was observed on weight of seeds per plant due to different phosphorus levels during the experimentation (Table 6).…”
Section: Weight Of Seeds Per Plant (G)supporting
confidence: 59%
“…15 th October sowing dates of fenugreek was found to be on par with 1 st November in case of higher fresh weight of leaf, dry weight of plant, leaf area, seed yield, chlorophyll content, diosgenin content and protein content (Anitha et al 2016) [2] . Sowmya (2016) [18] observed that growth of fenugreek plant, weight of plant was maximum when planted on 10 th Oct. The maximum number of days taken (53.33 days) to 50% flowering was recorded with 25 th September sowing and minimum number of days taken to 50% flowering were recorded under 9 th November.…”
Section: ) Effect Of Different Sowing Timementioning
confidence: 98%